Understanding the motivations behind dating applications: exploring future predictions - Davis, Dane Anthony (Kansas State University, 2018)
This exploratory research utilized focus groups from college students to learn how and why people are using current mobile dating applications to form and maintain relationships. Additionally, the author asked participants about their perception of a new mobile application that is still in the conceptual stages called Flick. The results revealed seven key themes to the gratifications people receive from mobile dating apps: (Theme 1: Dating Applications as Games and Entertainment; Theme 2: Perceptions of App Functions Vary by Gender; Theme 3: Dating Applications to Embrace Hookup Culture/Casual Sex; Theme 4: Dating Applications as the Lottery Ticket for Love/Relationship Seeking; Theme 5: Dating Applications as Self-Validation; Theme 6: Dating Applications for Social Means; Theme 7: Dating Applications as Trendiness) Lastly, the overall perceptions of Flick were very positive from all sessions. However, when it comes to the dating component of the application, the users were much more uncertain. Due to this finding, the author has decided to take the branding and purpose of Flick to only focus on the business and friend components.
Keywords: Online dating; Applications; Flick; Gratifications